An Analysis of Teachers' Questioning Strategies to Attract Students' Activeness and Curiosity in the Classroom Interaction - Abdul Rahman; Nurdevi Bte Abdul; Andi Bulkis Maghfirah Mannong (FKIP Unismuh Makassar, 2023)
The purpose of this study were to find out (1) what types of questioning strategies the English teachers used to attract students' activeness and curiosity in the classroom interaction and (2) what are students’ responses on teachers’ questioning strategies at SMP Muhammadiyah Limbung. The subject of this research are 2 English teachers and 6 students with purposive sampling technique. The object of this research are to find out what types of questioning strategies the English teachers used in the classroom interaction and what are students’response on the teachers’ questioning strategies. This research used descriptive qualitative method. Data collected from classroom observation class with field notes and interview. Data analysis is divided into three stages: data reduction, data display, and verification (conclusion drawing).The results of this research was English teachers of SMP Muhammadiyah Limbung used questioning strategies. They used probing questioning strategy and factual questioning strategy. They used some of classification probing questioning strategy, they were prompting probing question, clarifying question and switching probing question. The teachers used probing questioning strategy, especially for using prompting probing question is to make students more excited to answer the question with some clues from their teacher. And then, using clarifying probing question is to make students remember the material that their teacher had been given them before and next, using switching probing question is to give the chance for the other students to answered the question when their friend answered the question, so they can discuss about their answer and make it conclusion to find the right answer. And also they used factual questioning strategy to require the students to recall specific information students have learned. It can conclude that used questioning strategies was very helpful for the teachers to make their students more active in the class and help them to understand about the material delivered by the teacher.